2004
DOI: 10.1007/s00520-004-0658-6
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised evaluation of G-CSF or G-CSF plus oral antibiotics in chemotherapy-treated patients at high risk of developing febrile neutropenia

Abstract: The use of G-CSF for the secondary prevention of FN is extremely effective and allows the maintenance of chemotherapy dose intensity. Our study showed that the addition of antibiotics does not seem to be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Similar results were reported in a more recent study, in which 48 patients with various tumors and having received different chemotherapies, and who all experienced an episode of febrile neutropenia during the first cycle, received prophylaxis with GCSF during a subsequent course of the same chemotherapy without reduction in the dose intensity; the frequency of febrile neutropenia was 2% (one out of 48 patients) [11].…”
Section: Secondary Prophylaxissupporting
confidence: 80%
“…Similar results were reported in a more recent study, in which 48 patients with various tumors and having received different chemotherapies, and who all experienced an episode of febrile neutropenia during the first cycle, received prophylaxis with GCSF during a subsequent course of the same chemotherapy without reduction in the dose intensity; the frequency of febrile neutropenia was 2% (one out of 48 patients) [11].…”
Section: Secondary Prophylaxissupporting
confidence: 80%
“…Chemotherapy-induced (CIN) and febrile neutropenia (FN) are potentially life-threatening complications of myelosuppressive chemotherapy, may often require hospitalization, and may result in disruptions to the planned chemotherapy regimen [1][2][3][4][5]. Known risk factors for CIN/FN enable clinicians to risk-stratify patients and initiate prophylaxis with granulocyte colony-stimulating factors (GCSF) [1,3,[6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have suggested that the use of prophylactic G-CSF, antibiotics and pegfilgrastim for the secondary prevention of FN is extremely effective and allows the maintenance of chemotherapy dose intensity (Lalami et al, 2004;Jenkins et al, 2012). Based on these studies, We are cautiously considering using hematopoietic growth factors and advances in antibiotic therapy on docetaxel-Based Systemic Chemotherapy with CRPC in the next study.…”
Section: Discussionmentioning
confidence: 99%